NONFORMAL SEGMENT DEVELOPMENT IN LIFE LONG LEARNING - Pavlyk, Nadiia (Continuing Professional Education: Theory and Practice, 2019)
In the article is analyzed the meaning of the category “life long learning” which is based on semantic analysis of its using in the literature. Here the social background of the concept of constant education development is summarized. Conceptual principles and contradictions change of role and content of education are defined. It is determined that the structure of constant education consists of formal, non-informal and informal educational systems. In Ukrainian educational area the components of constant education are life long learning, adult education and non-formal education. Author analyses the process of constant education development. It is found that non-formal education existed throughout the period of the educational system development in the form of innovation, which is in the process of confirmation of efficiency and effectiveness, shifted from non-institutional system into institutional learning system. It is concluded that the development of educational systems is a response to social changes, which is based on the need for resolving contradiction to individual and social needs. The category “life long learning” covers the spectrum of interpretations and values to describe the different states of education, includinginformaleducation. Periodization phases of constant education depend on the object of study, but most scientists conclude that modern character is tic of constant educationis a grow in grole, and thus the spread of non-formal learning.